QUATERNARY SEDIMENTATION AND SUBSIDENCE HISTORY OF LAKE BAIKAL, SIBERIA, BASED ON SEISMIC STRATIGRAPHY AND CORING - Colman S.M.; Karabanov E.B.; Nelson III C.H. (My University, 2003)
The long, continuous, high-latitude, stratigraphic record of Lake Baikal was deposited in three broad sedimentary environ-ments, defined by high-resolution seismic-reflection and coring meth-ods: (1) turbidite depositional systems, by far the most widespread, characterizing most of the margins and floors of the main basins of the lake, (2) large deltas of major drainages, and (3) tectonically or topographically isolated ridges and banks. Holocene sedimentation rates based on radiocarbon ages vary by more than an order of mag-nitude among these environments, from less than about 0.03 mm/yr on ridges and banks to more than about 0.3 mm/yr on basin floors. Ex-trapolating these rates, with a correction for compaction, yields ten-tative estimates of about 25 and 11 Ma for the inception of rifting in the Central and North basins, respectively, and less than 6 Ma for the 200-m sediment depth on Academician Ridge. The Selenga Delta has the distinctive form of a classic prograding Gilbert-type delta, but its history appears to represent a complex com-bination of tectonism and sedimentation. The central part of the delta is underlain by prograding, shallow-water sequences, now several hun-dred meters below the lake surface. These deposits and much of the delta slope are mantled by fine-grained, deep-water, hemipelagic de-posits whose base is estimated to be about 650,000 years old. Modern coarse-grained sediment bypasses the delta slope through fault-con-trolled canyons that feed large, subaqueous fans at the ends of the South and Central basins. These relations, along with abundant other evidence of recent faulting and the great depths of the Central and South basins, suggest that these two rift basins have experienced a period of unusually rapid subsidence over the last 650,000 years, dur-ing at least part of which sedimentation has failed to keep pace.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная